COMMUNITY STRUCTURE AND SPATIAL DISTRIBUTION OF FISH JUVENILE IN MANGROVE AND SEAGRASS HABITATS IN PRAMUKA ISLAND - Fathul Amin; M Mukhlis Kamal; Am Azbas Taurusman (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2016)
This study was aimed to investigate the community structure of fish juvenile, spatial distribution and similarity from both adjacent habitats of mangrove and seagrass. This study was conducted in the eastern part of Pramuka island from April to June 2015. The samples were collected by using line transect method in three observation areas that were spatially connected i.e., mangrove, transition and seagrass zones. The result of the study from three observation zones revealed that there were found 24 species of fishes from 15 families i.e., Siganidae (4 species), Apogonidae (3 species), Ger-reidae (2 species), Terapontidae (2 species), Gobiidae (2 species), Labridae (2 species), Mugilidae, Nemipteridae, Hemiramphidae, Sphyraenidae, Monacanthidae, Atherinidae, Pomacentridae, Lut-janidae, and Lethrinidae (each of them 1 species). According to community structure, the adjacent ob-servation zones did not show a significant difference in the number of species, abundance, and bio-mass. According to fish distribution, fish species in transition zone and seagrass zone were relatively similar and dominated by Gerres oblongus, Fibramia lateralis, and Siganus canaliculatus. Mean-while, in mangrove zone revealed a significant different of fish species than in transition and seagrass zones. In mangrove zone, fish species was dominated by Gerres oblongus and Siganus guttatus. Keywords: spatial distribution, juvenile, mangrove, seagrass, pramuka Island, Siganidae